NILAI KEISLAMAN DALAM PUISI GUGURITAN SUNDA DI JAWA BARAT - Rima Sarah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
The footprint of Islam in the archipelago has encouraged the development of Islamic intellectual traditions in several regions of the archipelago. The diversity of religious local creativities contained in the Islamic scientific tradition triggers a wider development. Guguritan or Sundanese metrical poetry is one type of local element that colors the Islamic scientific tradition in West Java. The method used is literary structuralism approach, this research is focused on journalism as part of the Islamic scientific creativity. The research focuses on the influence of Islam on Sundanese literature, the development of Guguritan poetry, and its position in the Islamic scientific tradition in West Java. The object of this research is the poetry of the Sundanese Guguritan which creates a local symbolic image of Islamic values in West Java. The findings in this study are that the Guguritan is used in more or less three Islamic scientific traditions, namely Sufism, Al-Qur'an interpretation, and notes on the pilgrimage. The result of the research is that the interpretation of the Al-Qur'an in the form of a declaration can create a poetic nuance, while Sufism is much more complex than other poetic translations. Then, the pilgrimage has its own historical value. The conclusion of this study focuses on the various kinds of Islamic themes as evidence that Islamic literature has an important role in the process and development of Indonesian language and literature, especially West Java.Key words: The footprint of Islam in the archipelago has encouraged the development of Islamic intellectual traditions in several regions of the archipelago. The diversity of religious local creativities contained in the Islamic scientific tradition triggers a wider development. Guguritan or Sundanese metrical poetry is one type of local element that colors the Islamic scientific tradition in West Java. The method used is literary structuralism approach, this research is focused on journalism as part of the Islamic scientific creativity. The research focuses on the influence of Islam on Sundanese literature, the development of Guguritan poetry, and its position in the Islamic scientific tradition in West Java. The object of this research is the poetry of the Sundanese Guguritan which creates a local symbolic image of Islamic values in West Java. The findings in this study are that the Guguritan is used in more or less three Islamic scientific traditions, namely Sufism, Al-Qur'an interpretation, and notes on the pilgrimage. The result of the research is that the interpretation of the Al-Qur'an in the form of a declaration can create a poetic nuance, while Sufism is much more complex than other poetic translations. Then, the pilgrimage has its own historical value. The conclusion of this study focuses on the various kinds of Islamic themes as evidence that Islamic literature has an important role in the process and development of Indonesian language and literature, especially West Java.